Territorial investigations (Amsterdam : Rodopi, 1999)
Nowadays there are many spaces of fascination in visual art. Of course, installative space and contextual space have been on the art scene for awhile. However, they are now accompanied by other spaces such as urban space, architectural space, cyberspace, hyperspace, and screen-based space. In this volume, architects, artists, theorists, three symposia and four exhibitions attempt to find answers to questions such as: Could the architectonic study and/or deconstruction of space play a decisive role in the shift of attention to space? Which theoretical factors structure the current experience and meaning of space? What is the role of the aesthetization of the environment on our concept of space? Smooth Space - VCC de Brakke Grond, Amsterdam - is a project at the heart of this publication. Spatial interests range from how the concept of space is redefined and exploited in our current visual culture to how the digital world influences our spatial concepts.
Also issued online.
boek
Keywords: Space (Art); Space (Architecture); Space and time; Space and time; Space (Architecture); Space (Art); Environments